2021
DOI: 10.1093/ibd/izab236
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Outcomes in Patients With Inflammatory Bowel Disease: Systematic Review and Meta-Analysis

Abstract: Background Our understanding of coronavirus disease 2019 (COVID-19) and its implications for patients with inflammatory bowel diseases (IBD) is rapidly evolving. We performed a systematic review and meta-analysis to investigate the epidemiology, clinical characteristics, and outcomes in IBD patients with COVID-19. Methods We searched PubMed, EMBASE, Cochrane Central, Clinicaltrials.gov, Web of Science, MedRxiv, and Google Sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 53 publications
1
56
0
4
Order By: Relevance
“…In one meta-analysis, pooled relative risks of hospitalisation (RR 0.34, 95% CI 0.19 to 0.61), ICU admission (RR 0.49, 95% CI 0.33 to 0.72) and mortality (RR 0.22, 95% CI 0.13 to 0.38) were lower in biological-treated patients, most of whom were on anti-TNF, compared with patients treated with other non-biologicals for IBD 30. A meta-analysis also found that patients treated with anti-TNF therapy had decreased risk of hospitalisation and ICU admission compared with corticosteroids or 5-ASA 56…”
Section: Impact Of Ibd On Covid-19mentioning
confidence: 96%
See 2 more Smart Citations
“…In one meta-analysis, pooled relative risks of hospitalisation (RR 0.34, 95% CI 0.19 to 0.61), ICU admission (RR 0.49, 95% CI 0.33 to 0.72) and mortality (RR 0.22, 95% CI 0.13 to 0.38) were lower in biological-treated patients, most of whom were on anti-TNF, compared with patients treated with other non-biologicals for IBD 30. A meta-analysis also found that patients treated with anti-TNF therapy had decreased risk of hospitalisation and ICU admission compared with corticosteroids or 5-ASA 56…”
Section: Impact Of Ibd On Covid-19mentioning
confidence: 96%
“…Conflicting results have been reported on the effect of 5-aminosalicylic acid (5-ASA) on the disease course of COVID-19 in patients with IBD. Several studies conducted early in the pandemic, including two meta-analyses, demonstrated an increased risk of critical care, ventilator use and mortality in those treated with 5-ASA compared with those not treated with 5-ASA 34 35 56. For instance, pooled relative risks was 1.59 for hospitalisation (95% CI 1.39 to 1.82), 2.38 for ICU admission (95% CI 1.26 to 4.48) and 2.62 for mortality (95% CI 1.67 to 4.11) in patients treated with 5-ASA 30.…”
Section: Impact Of Ibd On Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, however, the use of these therapies has been associated with an increased risk for bacterial and viral infections and viral reactivation [ 12 ]. Several authors have investigated the epidemiology, clinical characteristics, and outcomes in IBD patients with COVID-19, and a recent systematic review and meta-analysis of 14 studies including 50706 IBD patients with and without COVID-19 reported a low prevalence of COVID-19 in IBD patients and a worse outcome of COVID-19 in IBD patients receiving corticosteroids or mesalamine, while the use of anti-TNFs was associated with more favorable outcomes [ 13 ]. In contrast, there is no data about the prevalence and impact of Long COVID in IBD.…”
Section: Introductionmentioning
confidence: 99%
“…The cumulative experience of the last 2 years is in favor of continuing ongoing IBD therapy and not delaying the beginning of conventional immunomodulators or biological therapy because of the pandemic situation, in patients without COVID-19 [ 19 , 20 ].…”
Section: Discussion/conclusionmentioning
confidence: 99%